Pengetahuan dan Sikap Anak tentang Makanan Jajanan Sehat melalui Permainan Ular Tangga - Oslida Martony; Alfira Alfira; Eliska Eliska (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aimed to determine the knowledge and attitudes of healthy snack children through snake and ladder games in Lubuk Pakam sub-district. This research is a quantitative study with a quasi-experimental design of two groups of the pretest-posttest system. The results showed that by using the statistical test, the value of p = 0.000 <0.05. Based on the pretest and post-test results on 54 students, the average change in knowledge before the intervention was 12.8, and the closest intervention was 15.5. The shift in attitude before the intervention was 10.2, and after the intervention was 12.8. In conclusion, there is the influence of snake and ladder game counseling on healthy snack foods on elementary school children's knowledge and attitudes. Keywords: Healthy Snacks, Knowledge, Attitudes, Snakes, and ladders